Awareness & Utilization of National Rural Health Mission Services Among People of Selected Rural Areas in The State of Maharashtra - Ray, Suresh Kumar (National Journal of Community Medicine, 2014)
Objective: The present study on awareness & utilization of National Rural Health Mission services among rural people in Maharashtra was conducted keeping in mind to evaluate the percentage of people aware and utilize the NRHM services. Methods: Quantative research approach was adopted to conduct this study and the design used was exploratory survey. A Multiphasic Random Sampling was used for the selection of the representative samples for the study. Structured questionnaire on awareness, utilization, availability, factors affecting utilization and few open ended questions related to NRHM was given to the respondent’s. Validity and reliability of the tool was done following the scientific steps. Result: Most of the people (63%) were not aware about the different services under NRHM except Janani Suraksha Yojna. Finding of utilization depicted that majority (68.1%) of them had average utilization of NRHM Services. People (83%) have also responded that facilities were not good (in terms of infrastructure, drugs and equipment, availability of medical officers and nursing staff, transport etc.) in the government health settings and they have to wait for a long time to meet the doctors. Conclusion: The awareness and Utilization regarding National Rural Mission Services among people residing in rural area of the Maharashtra state is inadequate.